PATIENTS IN POST- CARDIAC SURGERY: CORRELATION BETWEEN TWO METHODS OF MEASURING BLOOD PRESSURE - Joice Cristiane Benetti; Marla Gonçalves Krewer; Emiliane Nogueira de Souza; Silvia Goldmeier (Universidade Federal de Santa Maria, 2013)
http://dx.doi.org/10.5902/217976928501 Aim: to verify the correlation about values of BP obtained by direct and indirect methods in patients in the postoperative cardiac surgery. Method: cross-sectional study, conducted between October to May 2011 in a postoperative unit of a hospital in Porto Alegre, Rio Grande do Sul, approved by number 4510.Included patient about both sex and ≥ 18 years with invasive brachial artery catheter. Simultaneously, after six hours post operative, the measurement of two methods was to made:first by the indirect method later by the direct method of another member side. Results: the sample included 142 patients, 63.8±11 years, 80 (56.3%) men.The correlations of the systolic and diastolic values were R=0.95 and 0.85respectively. Conclusion: among unstable patients, independent of the method of selecting, the indirect has proven reliable according criterion established in the guidelines.